If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = 15x + 40 Reorder the terms: Y = 40 + 15x Solving Y = 40 + 15x Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = 40 + 15x
| x^2-1x-9=3 | | 3x+11y=9 | | 4n-3=4n-2 | | 3a-4a+4= | | 2(x+1)+3(x-1)-(x-2)=9 | | Msquared+6m-16=0 | | 8+2x=x+20 | | 7x+2=44-7x | | 3x+6-12x=3(3x-2) | | m+26=13 | | -5x+6=x-54 | | 5x^3+4x^2-6x+1=0 | | x-10=-40+6x | | 9x+3=15x | | 47-x(3x+4)=2(17-2x) | | -3-5x=7x+45 | | 6x+4=7(x-7) | | -86=4-6(-2x+1) | | -86=4-6(-2x-1) | | 3x-2sqrt(x)-8=0 | | -7x+7=4x+7 | | (2x+3)(2x^2-5)= | | X+20=3x+4 | | 7x+2=x+20 | | 33/4x-(11/2)= | | 9+4x=2x+9 | | 2.5x+30=y | | c-3=2c+11 | | 33/4*(-11/2)= | | 325.00+6.44t=2500.00 | | 3x-2(4x-5)=16 | | -7/2n=49 |